Psychological Trauma Level Among Post Earthquake Children in Kajai West Pasaman West Sumatera - Jumilia; Kanathasan, Jayasree S. (International Journal of Natural and Health Sciences, 2024)
Indonesia is a country situated in the middle of two seas encircling continents. Indonesia is situated in the area of the world's most active earthquakes, as shown by its location on tectonic plates encircled by active volcanoes. Because of this, Indonesia is susceptible to a variety of natural calamities, including tsunami and eathquakes. An earthquake is a sudden, mild to strong shaking of the ground brought on by a shift in the earth's plates. Victims of earthquakes may have psychological and physical effects. For victims, it causes severe anguish and sadness. Examining the degree of trauma experienced by children following the earthquake in Kajai, West Pasaman, West Sumatra, Indonesia, is the goal of this study. In West Kajai Pasaman, West Sumatra, 303 post-earthquake children were the sample for this quantitative study, which used a descriptive research approach. According to the study's findings, mild trauma was experienced by 30.4% of post-earthquake children, moderate trauma by 62.7%, and severe trauma by 6.9% of the population. It is anticipated that this study would draw attention to the number of traumatized youngsters in Kajai village. The regulatory agencies will find these insights useful in reducing